The Process of Zeroization of the Indonesian Language in Makassar Language Speakers at SMAS IT Nurul Asafa Takalar - Ananda Aulya Natasya; Siti Suwadah Rimang; Ratnawati Ratnawati (International Journal Labs, 2026)
This study aims to describe the process of zeroization in the use of Indonesian by Makassar language speakers at SMAS IT Nurul Asafa Takalar. Zeroization is a phonological process involving the deletion of phonemic sounds for ease of articulation, which often occurs due to regional language interference with Indonesian. This study uses a descriptive qualitative approach, with data collection techniques comprising listening, recording, and note-taking of students' speech during learning activities. The results show that zeroization carried out by Makassar language speakers is divided into three forms, namely aphaeresis (loss of sound at the beginning of a word), apocope (loss of sound at the end of a word), and syncope (loss of sound in the middle of a word). For example, the word tetapi ('but') is pronounced as tapi (aphaeresis), presiden ('president') becomes presiden' (apocope), and bagaimana ('how') becomes gimana (syncope). This phenomenon reflects the strong influence of regional languages and informal language habits on students' Indonesian phonology. This research contributes to the understanding of phonological processes in a bilingual context and their implications for Indonesian language learning in schools.